Children with strabismus and amblyopia presented abnormal spontaneous brain activities measured through fractional amplitude of low-frequency fluctuation (fALFF) - Hu, Xiao-Qin; Shi, Yi-Dan; Chen, Jun; You, Zhipeng; Pan, Yi-Cong; Ling, Qian; Wei, Hong; Zou, Jie; Ying, Ping; Liao, Xu-Lin; Su, Ting; Wang, Yi-Xin; et al. (Frontiers in Neurology, 2022)
Purpose: Based on fMRI technology, we explored whether children with strabismus and amblyopia (SA) showed significant change in fractional amplitude of low-frequency fluctuation (fALFF) values in specific brain regions compared with healthy controls, and whether this change could point to the clinical manifestations and pathogenesis of children with strabismus to a certain extent. Methods：We enrolled 23 children with SA and same number matched healthy control in the ophthalmology department of the First Affiliated Hospital of Nanchang University, and the whole brain was scanned by rs-fMRI. The fALFF value of each brain area was derived to examine whether there is a statistical difference in the two groups. Meanwhile, ROC curve was made in a view to evaluate whether this difference proves useful as a diagnostic index. Finally, analyze whether changes in the fALFF value of some specific brain regions are related to clinical manifestations. Results：report to HCs children with SA presented a decreased fALFF values in left temporal pole: the superior temporal gyrus, right middle temporal gyrus, right superior frontal gyrus, right supplementary motor area. Meanwhile, they also showed higher fALFF values in specific brain areas, which included left precentral gyrus, left inferior Parietal, left Precuneus. Conclusion: Children with SA showed abnormal fALFF values in different brain regions. Most of these regions were allocated to the visual formation pathway. The eye movement-related pathway or other visual-related pathways, suggesting the pathological mechanism of the patient.